New taxonomical and ethnomycological observations on Psilocybe s.s. (Fungi, Basidiomycota, Agaricomycetidae, Agaricales, Strophariaceae) from Mexico, Africa and Spain - Guzmán, Gastón (Instituto de Ecología, A.C., 2012)
A new emendation of Psilocybe zapotecorum is presented, based on a new study on the holotype and on the description of pseudocystidia, pleurocystidia and cheilocystidia, confusingly described previously. An extensive and careful review of all holotypes of synonyms, and the wide neotropical distribution is also presented. The traditions as sacred mushroom are analyzed based on a study of codices and anthropological pieces, where P. zapotecorum and related species as P. muliercula and P. moseri are identified. Some of the codices and anthropological pieces showed that the cult of Quetzalcóatl was related to the use of these mushrooms. The application and meaning of the words “teonanácatl” from Sahagún and “teotlaquilnanácatl” by Guzmán are reviewed. Moreover, the relationship of P. mairei to the prehistoric mushroom depictions at Tassili in the Sahara Desert is discussed, and the first study of authentic material of this species from Algeria is presented, from where a neotype is selected. Finally, the relationship between a prehistoric mural in Spain and P. hispanica is also discussed.